2017
DOI: 10.1093/asj/sjx062
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Major Hematomas in Aesthetic Surgery: Analysis of 129,007 Patients

Abstract: Background: Postoperative hematomas are one of the most frequent complications following aesthetic surgery. Identifying risk factors for hematoma has been limited by underpowered studies from single institution experiences. Objectives: To examine the incidence and identify independent risk factors for postoperative hematomas following cosmetic surgery utilizing a prospective, multicenter database. Methods: A prospectively enrolled cohort of patients who underwent aesthetic surgery between 2008 and 2013 was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 51 publications
1
29
1
1
Order By: Relevance
“…However, the effect of combining these procedures on safety outcomes should also be considered. A previous study showed that combining esthetic surgery procedures increased the risk for major hematomas (Kaoutzanis et al, 2017). The present study of a cohort of 480 trans men confirms that hematoma of the chest and reoperation rates of the chest were both significantly higher in combined procedures (mastectomy and TLH ± BSO) compared with those in single masculinizing mastectomy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the effect of combining these procedures on safety outcomes should also be considered. A previous study showed that combining esthetic surgery procedures increased the risk for major hematomas (Kaoutzanis et al, 2017). The present study of a cohort of 480 trans men confirms that hematoma of the chest and reoperation rates of the chest were both significantly higher in combined procedures (mastectomy and TLH ± BSO) compared with those in single masculinizing mastectomy.…”
Section: Discussionsupporting
confidence: 83%
“…Smoking is thought to increase the risk of complications after surgery, however, reported effects of smoking vary. In a large cohort of esthetic surgical procedures, it was not found to be an independent predictor of postoperative hematoma (Kaoutzanis et al, 2017). Furthermore, hormone treatments are known to be prothrombotic.…”
Section: Discussionmentioning
confidence: 88%
“…Analysis of the belt lipectomy hematoma rates was also limited by a very low sample size (n = 30 in the concomitant group), and further research would be beneficial, especially given the notion that body region is a risk factor for hematoma occurrence and the acknowledgement of a paucity of data on this topic. 25 Overall, these results underscore the importance of carefully reporting the severity of hematoma in body contouring procedures, and the low overall incidence of hematomas necessitates large sample sizes to achieve adequate statistical power.…”
Section: Discussionmentioning
confidence: 79%
“… 11 In fact, the proportion of operative hematomas overall (around 1%) is more consistent with previously published reports on hematoma incidence in the literature, suggesting the possibility that the literature has a tendency to analyze operative over nonoperative hematomas. 25 , 26 The difference in conclusions between nonstratified and stratified hematoma data suggests that researchers should be more critical of studies that do not divide hematoma incidence into subgroups. These findings further emphasize that hematoma requiring re-operation is an inaccurate indicator of overall hematoma incidence, and it is essential for future studies to document and include minor hematomas treated in the outpatient setting to fully understand hematoma risk in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64][65] Risk factors for postoperative hematoma formation include anticoagulant use, older age, male gender, tobacco use, and medical comorbidities such as hypertension or malignancy. [66][67][68] Hematomas usually occur in the initial 24-hour postoperative period but have been reported months following the initial procedure. 61,69 Clinical presentation of hematomas depends on volume and rate of accumulation.…”
Section: Surgical Site Collectionsmentioning
confidence: 99%